The Impact of the Hospital’s Marketing Strategy on the Interest of Patient Visits Based on the Marketing Mix Approach at Boliyohuto Hospital - Ayuba, Silvana; Mohamad, Imelda; Lolo, Astria; Mooduto, Willian Indra S. (LPPM Universitas Bina Mandiri Gorontalo, 2021)
Due to the lack of the number of visits in March-December 2021, therefore, the current study aims to determine the influence of hospital marketing strategies on the interests of patient visits based on the marketing mix approach at Boliyohuto Hospital. This type of research is descriptive quantitative research. The respondents in the study were inpatients and outpatients at Boliyohuto hospital consisting of 188 respondents who were sampled using proportional random sampling with the Slovin formula to 65 respondents. The data collection was conducted using questionnaires which were then analyzed using the chi-square test. Research results of hospital marketing strategy on the interest of patient visits are P Value= 0.0 below <0.05 so that H0 is rejected and H1 is accepted. So there is an influence of hospital marketing strategy on the interest of patient visits in Boliyohuto Hospital. It can be concluded that Boliyohuto Hospital can carry out the right marketing strategy. The important thing to note is to maintain and improve more appropriate marketing strategies to meet market objectives and increase interest in future visits.